Le recours au Comité des droits de l'homme de l'O.N.U. : une illusion? - Côté, Marie-José (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1985)
The international charter of human freedoms became a legal reality via the coming into force of the following three documents : the International Convention on Economic, Social and Cultural Rights, the International Convention on Civil and Political Rights and the optional protocol attached to it. The Human Rights Committee was created under the Convention on Civil and Political Rights. In accordance with the controlling machinery set up under the optional protocol, the Committee must examine complaints from individuals who feel that their rights as defined and protected by the Convention, have been violated. Besides Uruguay, Canada is the country that submits the greatest number of complaints to the Human Rights Committee. To this days, six « communications » putting it into question have been at the origin of the adoption of « final views » two of which have demonstrated a violation of rights laid down in the Convention. Yet various improvements have proved to be desirable so as to make resorting to the Committee more efficient. It is even conceivable that making the rule on exhausting internal recourses might allow the Committee to influence Canadian law by inciting Canada to amend its Constitution or to integrate the Convention into its national law so as to be usable before the courts. The Committee has thereby contributed to increasing the basic freedoms of Canadians via the Convention on Civil and Political Rights. Although their accomplishments have been praiseworthy, work done by the Human Rights Committee risks being incomplete if the status quo continues.